Asymptomatic Hyperinsulinaemic Hypoglycaemia - Ana Ferreira; Mariana Serino Barbosa; Rita Coelho; Patrícia Lourenço (European Journal of Case Reports in Internal Medicine, 2020)
Hypoglycaemia is rare in apparently well patients without drug-treated diabetes mellitus and warrants evaluation and management when Whipple’s triad is present. Even in the absence of Whipple’s triad, when repeatedly low values of plasma glucose are documented, the presence of endogenous hyperinsulinism should be investigated. The authors describe a case of endogenous hypoglycaemic hyperinsulinism, its diagnosis and treatment and the challenges of determining its aetiology.